Legitimasi Pemilihan Umum di Indonesia Tahun 2019 - Untung Sri Hardjanto (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract The article aims to find out the legitimacy of the general elections in Indonesia in 2019, especially related to the future implementation of the basic constitution for holding the 2019 general election. Research is normative legal research based on the statutory approach. the results of the study indicate that legitimacy is the recognition and support of the community towards the winner of the election to then form a state government. So that legitimacy is needed for political stability and the possibility of social change and opening opportunities to expand fields in order to improve welfare. For Indonesia, the 2019 Election will receive formal-procedural legitimacy from anyone considering the existence of institutions that carry out the implementation of elections based on the principle of overflow. Whereas the legitimacy that is based on personal characteristics will only be a comparison and directing, leading to the voting of the people, will not affect the government formed given the existence of peaceful and democratic election pacts and the media that has arrived in the regions. Keywords: Legitimacy, Constitution, General Elections, Jurdil, and Luber Abstrak Artikel bertujuan untuk mengetahui legitimasi pemilihan umum di Indonesia tahun 2019, khususnya terkait dengan masa depan pelaksanaan dasar konstitusi penyelenggaraan pemilihan umum 2019. Penelitian merupakan penelitian hukum normatif yang berdasarkan pada pendekatan statutory approach. hasil penelitian menjukkan bahwa legitimasi merupakan pengakuan dan dukungan dari masyarakat terhadap pemenang pemilu untuk kemudian membentuk pemerintahan negara. Sehingga legitimasi diperlukan untuk kesetabilan politik dan kemungkinan terjadinya perubahan sosial serta membuka kesempatan memperluas bidang-bidang dalam rangka peningkatana kesejahteraan. Untuk Indonesia, Pemilu Tahun 2019 akan mendapat legitimasi formal-prosedural dari siapapun mengingat adanya lemabaga negara yang menjalankan penyelenggaraan pemilu berdasar pada asas luber jurdil. Sedangkan legitimasi yang mendasarkan pada ciri pribadi hanya akan menjadi pembanding dan mengarahkan, menggiring menuju pemberian suara masyarakat, tidak akan berpengaruh pada pemearintahan yang terbentuk mengingat adanya pakta pemilu damai dan demokratis serta mas media yang sudah sampai kedaerah. Kata Kunci: Legitimasi, Konstitusi, Pemilihan Umum, Jurdil dan Luber